Face Sketch to Photo Matching Through Dynamic Local Feature Extractions and Cascaded Static - Pandey, Chetan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
By using a method of cascading static and dynamic local feature extraction, we attempt to deal with the identification of a photo from a face sketch effect of these effects in this process. To ensure that the feature vectors created are depending upon the appropriate patches. Along with that approach, we include the closest neighbours technique for matching sketches and photos, which concatenates the feature vectors obtained from local static extraction. Following the extraction of the image's characteristics, the most comparable images are narrowed down based on their closes neighbours. Eventually, feature vectors from the local dynamic extraction approach are used to rematch these images. The closest neighbours technique is used to match the feature vectors. The major goal of this technique is to increase the detection system's precision while simultaneously increasing recognition rates and feature stability.